Decadal Disruption of the QBO by Tropical Volcanic Supereruptions. Issue 5 (9th March 2021) - Brenna, Hans; Kutterolf, Steffen; Mills, Michael J.; Niemeier, Ulrike; Timmreck, Claudia; Krüger, Kirstin
Abstract: The Los Chocoyos (14.6°N, 91.2°W) supereruption happened ∼75, 000 years ago in Guatemala and was one of the largest eruptions of the past 100, 000 years. It emitted enormous amounts of sulfur, chlorine, and bromine, with multi‐decadal consequences for the global climate and environment. Here, we simulate the impact of a Los Chocoyos‐like eruption on the quasi‐biennial oscillation (QBO), an oscillation of zonal winds in the tropical stratosphere, with a comprehensive aerosol chemistry Earth System Model. We find a ∼10‐year disruption of the QBO starting 4 months post eruption, with anomalous easterly winds lasting ∼5 years, followed by westerlies, before returning to QBO conditions with a slightly prolonged periodicity. Volcanic aerosol heating and ozone depletion cooling leads to the QBO disruption and anomalous wind regimes through radiative changes and wave‐mean flow interactions. Different model ensembles, volcanic forcing scenarios and results of a second model back up the robustness of our results. Plain Language Summary: Supereruptions are some of the most violent natural events on Earth which can erupt approximately every 100, 000 to 200, 000 years. Here, we investigate the impact of the Los Chocoyos (14.6°N, 91.2°W) eruption ∼75, 000 years ago in Guatemala on the atmospheric circulation in the tropics (30°S to 30°N). The dominating circulation phenomenon in the tropical stratosphere, the second layer of the atmosphere at ∼16–50 km altitude in the tropics, is the quasi‐biennial oscillation (QBO) an approximately 28 months oscillation of alternating easterly or westerly winds occurring symmetrically between 15°S and 15°N. Using an Earth System Model taking volcanic aerosol chemistry climate interactions into account, we study the QBO response to this violent volcanic eruption. Our model results show a disruption of the QBO for up to 10 years before a return to a QBO regime with a slightly longer period. The direct injection of volcanic sulfur and halogens into the stratosphere leads to sulfuric acid droplet formation and ozone depletion impacting atmospheric radiation and dynamics which disturb the QBO wind system. Key Points: Los Chocoyos sulfur‐ and halogen‐rich supereruption Volcanic forcing changes chemistry, radiation, and dynamics Super volcanic eruption disrupts the Quasi Biennial Oscillation